2020
DOI: 10.1007/s10822-020-00332-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Epac1 interactions with the allosteric inhibitor AM-001 by co-solvent molecular dynamics

Abstract: The exchange proteins activated by cAMP (EPAC) are implicated in a large variety of physiological processes and they are considered as promising targets for a wide range of therapeutic applications. Several recent reports provided evidence for the therapeutic effectiveness of the inhibiting EPAC1 activity cardiac diseases. In that context, we recently characterized a selective EPAC1 antagonist named AM-001. This compound was featured by a non-competitive mechanism of action but the localization of its alloster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…AM-001 also reduces pathological cardiac remodeling in C57BL/6 mice treated with ISO ( Laudette et al, 2019 ). Another study showed that AM-001 can improve the contact between the CDC25-HD and CNBD domains which stabilizes the inactive conformation ( Bufano et al, 2020 ; Yang et al, 2021a ; Zhang et al, 2021 ).…”
Section: Inhibitors and Activatorsmentioning
confidence: 99%
“…AM-001 also reduces pathological cardiac remodeling in C57BL/6 mice treated with ISO ( Laudette et al, 2019 ). Another study showed that AM-001 can improve the contact between the CDC25-HD and CNBD domains which stabilizes the inactive conformation ( Bufano et al, 2020 ; Yang et al, 2021a ; Zhang et al, 2021 ).…”
Section: Inhibitors and Activatorsmentioning
confidence: 99%